Use of Stereolithographic Templates for Surgical and Prosthodontic Implant Planning and Placement. Part II. A Clinical Report - Kunal Lal, DDS, MS;1 George S. White, DDS;2 Dennis N. Morea, DDS;2 (Journal of Prosthodontics, 2006)
Eight implants were placed in the posterior part of the mandible using computer-generated stereolithographic templates